From the Ptolemies to the Romans political and economic change in Egypt - Monson, Andrew 1977- (Cambridge University Press, 2012)
This book gives a structured account of Egypt's transition from Ptolemaic to Roman rule by identifying key relationships between ecology, land tenure, taxation, administration and politics. It introduces theoretical perspectives from the social sciences and subjects them to empirical scrutiny using data from Greek and Demotic papyri as well as comparative evidence. Although building on recent scholarship, it offers some provocative arguments that challenge prevailing views. For example, patterns of land ownership are linked to population density and are seen as one aspect of continuity between the Ptolemaic and Roman period. Fiscal reform, by contrast, emerges as a significant mechanism of change not only in the agrarian economy but also in the administrative system and the whole social structure. Anyone seeking to understand the impact of Roman rule in the Hellenistic east must consider the well-attested processes in Egypt that this book seeks to explain
Keywords: Geschichte 200 v.Chr.-150; Geschichte; Politik; Wirtschaft; Human geography / Egypt / History; Social structure / Egypt / History; Land tenure / Egypt / History; Politischer Wandel; Wirtschaftsentwicklung; Egypt / History / Greco-Roman period, 332 B.C.-640 A.D.; Egypt / Politics and government / 332-30 B.C.; Egypt / Politics and government / 30 B.C.-640 A.D.; Egypt / Economic conditions / 332 B.C.-640 A.D.; Ägypten -- Altertum